2009
DOI: 10.1002/ddr.20288
|View full text |Cite
|
Sign up to set email alerts
|

γ‐secretase inhibitors for the treatment of Alzheimer's disease

Abstract: Alzheimer's disease is a neurodegenerative disorder manifested by cognitive and memory deterioration, impairment of language, and other activities of daily life. Two major pathological hallmarks are characteristics of Alzheimer's disease: intracellular neurofibrillary tangles and extracellular amyloid plaques. The amyloid plaque is mainly comprised of aggregated form of the 40-42 residue amyloid bpeptide (Ab). The accumulation and deposition of Ab eventually lead to neuronal damage and cell death. Ab peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 64 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Long-term treatment with high doses of DAPT causes damage to organs, including intestine and kidney, which could limit the potential clinical use of this class of reagents (33). Our DAPT regimen did not affect liver, lung, small intestine, or kidney at the microscopic level, nor did it affect body weight or survival (Supplemental Figure 7 and data not shown).…”
Section: Long-term Notch Inhibition By Dapt Prevents Bone Loss In Tnfmentioning
confidence: 90%
“…Long-term treatment with high doses of DAPT causes damage to organs, including intestine and kidney, which could limit the potential clinical use of this class of reagents (33). Our DAPT regimen did not affect liver, lung, small intestine, or kidney at the microscopic level, nor did it affect body weight or survival (Supplemental Figure 7 and data not shown).…”
Section: Long-term Notch Inhibition By Dapt Prevents Bone Loss In Tnfmentioning
confidence: 90%
“…Several potent, small-molecule GSIs have been developed (Olson and Albright, 2008;Wu and Zhang, 2009). Structurefunction studies have shown that GSIs selected for in vivo use, the azepines and sulfonamides, bind a common allosteric inhibitory site on presenilin (PS), rather than the site targeted by GSIs in the isostere class and are believed to interact with the active site of the enzyme (Olson and Albright, 2008;Steiner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…␥-Secretase activity is required for signaling by the Notch-family of transmembrane receptors. Inhibition of Notch signaling could cause gastrointestinal toxicity and mechanism-based side effects [9,10]. Therefore, the selectivity for inhibition is critical for the drug efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%